(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The words in one group of a stable compound combine in terms of meaning and create meaningful unity. Often the meaning is equal to one word and is portable. Such a stable combination of words is a phrase (phraseological unit). A language unit consisting of two or more words and expressing a single meaning is called a phrase. A special branch of linguistics that studies phrases is called phraseology. Phraseology means "the science of phrases" in Greek.